Decision tool of medical endoscope maintenance service in Chinese hospitals: a conjoint analysis - Zheng, Jun; Wei, Jingming; Xie, Ying; Chen, Siyao; Li, Jun; Lou, Ligang; Sun, Jing; Feng, Jingyi (BioMed Central, 2023)
Medical devices are instruments, apparatus, appliances, software, implants, reagents, materials or other articles that are intended for use in the treatment or diagnosis of disease or injury in humans. Concerning medical endoscope devices, which enable doctors to observe and manipulate the area under examination through a puncture hole in the body cavity or organ, hospitals predominantly consider the quality and cost of maintenance services when making their selection. The effective and efficient provision of maintenance services plays a crucial role in ensuring cost-effective and high-quality management of medical devices. In this study, we have developed an innovative decision tool that analyzed key factors impacting the choice of medical devices’ maintenance service. This tool assists hospitals in evaluating and selecting appropriate maintenance services for medical device, specifically endoscopy devices. Moreover, it also serves as a valuable resource for manufacturers and suppliers to enhance their after-sales service offerings.
Keywords: Medical endoscope; Maintenance service demands; Decision-making; Conjoint analysis